Impact of dose intensified salvage radiation therapy on urinary continence recovery after radical prostatectomy: Results of the randomized trial SAKK 09/10. Issue 2 (February 2018) - Ghadjar, Pirus; Hayoz, Stefanie; Bernhard, Jürg; Zwahlen, Daniel R.; Stein, Jürgen; Hölscher, Tobias; Gut, Philipp; Polat, Bülent; Hildebrandt, Guido; Müller, Arndt-Christian; Putora, Paul Martin; Papachristofilou, Alexandros; et al.
Abstract: Introduction: Adjuvant radiation therapy (aRT) after radical prostatectomy (RP) is associated with impaired urinary continence recovery as compared to surveillance. Less is known regarding the effect of salvage radiation therapy (sRT) dose intensification on continence outcomes. Materials and methods: Urinary continence recovery was investigated within a multicentre randomized trial in biochemically recurrent prostate cancer patients who received either 64 Gy (32 fractions) or 70 Gy (35 fractions) sRT. Incontinence was assessed using Common Toxicity Criteria for Adverse Events v4.0 at baseline, at the end of sRT and 3 months afterward. Quality of life (QoL) was assessed with the EORTC QoL questionnaires C30 and PR25 at baseline and 3 months after completion of sRT. A total of 344 patients were evaluable. Results: At baseline 233 (68%) of patients were fully continent and 14% in both arms became incontinent three months after treatment. Of the remaining 111 (32%) patients being incontinent at baseline, continence recovery was achieved 3 months after sRT by 44% vs. 41% with 64 vs. 70 Gy, respectively ( p = 0.8). This analysis is limited by its short follow-up. Conclusions: Dose intensification of sRT had no impact on early urinary continence recovery or prevalence of de novo incontinence.